Uranium inhibits mammalian mitochondrial cytochrome c oxidase and ATP synthase. (15th February 2021) - Yu, Libing; Li, Wenjing; Chu, Jian; Chen, Chun; Li, Xijian; Tang, Wei; Xia, Binyuan; Xiong, Zhonghua
Abstract: As an emerging pollutant, uranium poses serious concerns to ecological and human health. The kidney has been established as a major deposition site and the most sensitive target organ for uranium poisoning, and the underlying toxicological mechanisms have been associated with oxidative stress and mitochondrial respiration. However, the identities of key molecular targets in uranium-induced toxicity remain elusive. In this study, we comprehensively evaluated the in vitro effects of uranium on ten critical enzymes in the mitochondrial respiration pathway and discovered that respiratory chain complex IV (cytochrome c oxidase) and complex V (ATP synthase) were strongly inhibited. The inhibitory effects were validated with mitochondria from human renal proximal tubule cells—the most affected renal site in uranium poisoning. The IC50 values (around 1 mg/L) are physiologically relevant, as they are comparable to known kidney accumulation levels in uranium poisoning. In addition, these inhibitory effects could explain the well-documented uranium-induced reactive oxygen species generation and mitochondrial alterations. In conclusion, cytochrome c oxidase and ATP synthase are possibly key molecular targets underlying the toxic effects of uranium. Graphical abstract: Image 1 Highlights: Effects of uranium on mitochondrial respiration are comprehensively evaluated. Uranium inhibits human mitochondrial cytochrome c oxidase and ATP synthase. The IC50 values (around 1 mg/L) are comparable to renal levels in uranium poisoning. Abstract : Mitochondrial cytochrome c oxidase and ATP synthase are identified as potential molecular targets underlying the nephrotoxicity of uranium.